Psoriatic arthritis as a mountain - J.M. Berthelot (Reumatismo, 2003)
There is no doubt that inflammatory arthritis/enthesitis and psoriasis coexist more frequently than would be expected by chance: for instance, in a study of 1285 patients with psoriasis seen in an hospital, 483 (38%) were suffering from arthritis/ enthesitis, including 40 patients classified as Rheumatoid Arthritis (RA) (3%), 177 (14%) as undifferentiated arthritis (UA), and 266 (21%) as Psoriatic Arthritis (PsA) (1). Although lower percentages have been noticed in the general population with psoriasis (6% of PsA in an extensive study of 1844 patients with psoriasis) (2), they were superior to 5% (i.e. at least 5 times greater than the figures found for patients without psoriasis) (3-7).